Wybrane zagadnienia dotyczące wykorzystania umowy cywilnoprawnej jako instrumentu działania administracji - Fermus-Bobowiec, Anna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Public administration entities are parties to civil-law contracts in the non-regulatory area. A characteristic feature of such contracts is their subordination to civil law regulations, but with modifications resulting from special legal provisions. These modifications are, due to the fact that one of the parties to the contract is a public entity which, by concluding the contract, acts in a public interest and caters for public needs. In the legal practice, the most frequent civil-law contracts concluded by administration entities are public procurement contracts. Their special status is based on the Act of 29 January 2004 – the Public Procurement Law (Journal of Laws of 2017, item 1579 as amended) and is subordinate to the basic purpose of the Act, that is ensuring that the entities from a widely understood public sector conclude civil-law contracts under optimum terms and conditions. The civil-law contracts are discussed from the perspective of their subject- and object-related classification, mode of conclusion, form of a contract and its duration, shaping its contents, amendments, termination and annulment.